Effects of intellectual capital information disclosed in annual reports on market capitalization: evidence from Bursa Malaysia - Anam, Ousama Abdulrahman; Abdul Hamid , Fatima; Ab. Rashid, Hafiz Majdi (Emerald Group Publishing Limited, 2011)
This paper aims to examine the effects of intellectual capital (IC) disclosure in the annual reports of listed companies in Bursa Malaysia (BM) on their market capitalization (MCAP).